Measurement of “behavior” or “intention to behaviors” in MS theses of Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences - Yaghmaei, F; Dakhte Haruoni, M; Mottaghi, B (Advances in Nursing & Midwifery, 2009)
Background and aim Behavior and performance are investigated in different studies, which yields significant information to researchers leading to discovery of weak and strong points of behavior. This plays an important role in reaching to research goals. This review study was carried out to identify methods in the measurement of behaviors and application of them in MS theses of students in faculty of nursing and midwifery of Shahid Beheshti Medical University. Materials and methods 526 MS theses of students were investigated in terms of the methods for measurement or evaluation of behaviors. Findings Of the 526 theses, 22 were related to the measurement of behavior. Behaviors were measured by self-report questionnaires, checklist and no tool in 12, 8 and 2 theses respectively. Conclusion Findings showed that behavior is mostly measured by questionnaire and less by observation which yields more complete information. Keywords: Behaviour measurement, Reasoned Action Theory, Questionnaire, Observation. *Corresponding Author: Dr. Yaghmaei; Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, <span style="font-size: 12pt; font-family: ";Times New Roman";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-language: FA; mso-bidi-font-family: 'B Nazanin'; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">Shahid<span style="font-size: 12pt; font-family: ";Times New Roman";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-language: FA; mso-bidi-font-family: 'B Nazanin'; mso-ansi-language: EN-US; mso-fareast-language: EN-US;"> Beheshti University of Medical Sciences, Shariati, Tehran, Iran. E-mail: Farideh_y2002@yahoo.com